Random Perforator Flap : Some Experiences with Keystone Flap - Sudjatmiko, Gentur; Pribadi, Sweety; Supit, Laureen (Jurnal Plastik Rekonstruksi, 2013)
Background: In reconstructing challenging defects, surgeons are considered fairly fortunate when they are able to obtain a similar donor tissue quality to that of the missing tissue; in regards to their color, texture, size, and the ease of donor transfer to the defect. Several methods may be used, which frequently include the free tissue transfers using microvascular anastomoses bearing their specific consequences. We report a select of challenging cases which were successfully reconstructed using the Keystone flaps and avoid microvascular anastomoses, where otherwise the free tissue transfers would be the typical option for closure in such defects. Patient and Method: Nine cases of relatively large defect in various locations were reconstructed using the Keystone flaps supplied by either non-identified perforators or identified reliable perforators. Result: Out of the 9 defects located on various region of the body (lumbar, thorax, dorsum of the foot, plantar of the foot, posterior leg, sacrum, and cervicofacial) only the first 2 cases had identifiable perforators. All flaps survived completely without problem of vascularization. Summary: The Keystone flap is a useful and reliable random perforator-based flap even when the perforator vessels are not identified.